2005
DOI: 10.1111/j.1468-2303.2005.00344.x
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Russian Imperial History

Abstract: Path dependency is a most valuable tool for understanding Russian history since 1480, which coincides with the ending of the "Mongol yoke," Moscow's annexation of northwest Russia, formerly controlled by Novgorod, and the introduction of a new method for financing the cavalry-the core of a new service class. The cavalry had to hold off formidable adversaries (first Lithuania, then the Crimean Tatars, then the Livonians, the Poles, the Swedes, and the Ottomans) for Muscovy to retain its independence. Russia in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Instead, the regression to cults of the ruler, the criminal-like nature of the ruling elite, the repressiveness and insecurity of property, and the reintroduction of the service state based on the concept of a "boyar"-like retinue around an allpowerful ruler all argue strongly for seeing contemporary Russia in the light of the medieval and feudal, if not Third World, analogy. Arguably, in many ways contemporary Russia resembles a feudal society and state, especially the Muscovite model postulated by many Western writers including this author (Baker and Glasser, 2005;Hellie, 2005;Rosefielde, 2004;Poe, 2003;Pipes, 1974;Balzer, 2005;Blank, 2007a;Hedlund, 2005). Indeed, Richard Hellie and Stefan Hedlund have suggested that, because time and again, Russia has reverted to this model of the patrimonial service state described here, its inclination to do so is path-dependent.-i.e., it is the same learned response to continuing challenges, which are all seen in the same light and therefore require the same answer or a similar one (Hellie, 2005;Hedlund, 2005).…”
Section: The Muscovite Model and Contemporary Russiamentioning
confidence: 88%
“…Instead, the regression to cults of the ruler, the criminal-like nature of the ruling elite, the repressiveness and insecurity of property, and the reintroduction of the service state based on the concept of a "boyar"-like retinue around an allpowerful ruler all argue strongly for seeing contemporary Russia in the light of the medieval and feudal, if not Third World, analogy. Arguably, in many ways contemporary Russia resembles a feudal society and state, especially the Muscovite model postulated by many Western writers including this author (Baker and Glasser, 2005;Hellie, 2005;Rosefielde, 2004;Poe, 2003;Pipes, 1974;Balzer, 2005;Blank, 2007a;Hedlund, 2005). Indeed, Richard Hellie and Stefan Hedlund have suggested that, because time and again, Russia has reverted to this model of the patrimonial service state described here, its inclination to do so is path-dependent.-i.e., it is the same learned response to continuing challenges, which are all seen in the same light and therefore require the same answer or a similar one (Hellie, 2005;Hedlund, 2005).…”
Section: The Muscovite Model and Contemporary Russiamentioning
confidence: 88%
“…В то же время петровская бюрократизация дворянства была тотальной. Было завершено построение того, что американский историк Р. Хелли назвал «служивым классом» (Hellie, 2005). Обязанность служить стала всеохватывающей и пожизненной.…”
Section: адаптационная модернизация в рамках петровских реформunclassified
“…Such structural re-formatting of the elites recurrently occurred in Russia. It may be interpreted as revolutions of service classes (Hellie 2005), or in terms of long modernization cycles (Wisniewski 1997), or as 'secular' structural cycles lasting for 200-300 years (Turchin and Nefedov 2009), etc. The conflict between the traditional feudal elite and royal power often occurred at the stage of the nation formation. The major lords supported centralization, but they themselves always turned out to be an obstacle to centralized governance.…”
Section: Fig 3 Russian Sociogenesismentioning
confidence: 99%